القراءات وعلومها عند الإمام الكواشي من خلال كتابه "التلخيص في تفسير القرآن العزيز": سورة الفاتحة أنموذجا - إسماعيل، أيمن إقبال محمد (جامعة الأزهر - كلية أصول الدين والدعوة بالزقازيق, 2022)
تناول البحث مسائل القراءات وعلومها الواردة في كتاب "التلخيص في تفسير القرآن العزيز" للإمام أبي العباس الكواشي (ت 680هـ)، من خلال عرض أنموذج لسورة الفاتحة، وذلك بدراسة تلك النصوص دراسة استقرائية وصفية، مع بيان لأهم معالم منهج المؤلف في تناوله لتلك المسائل، وتكمن مشكلة البحث في تعدد علوم القراءات الواردة في هذا التفسير، حتى بلغت سبعة علوم، دون وجود دراسة استقرائية تجمع شتاتها، وتوضح منهجها، ويتطلع الباحث إلى أن تكون هذه الدراسة نواة لدراسات استقرائية أخرى حول هذا الكتاب؛ تكشف أهم معالمه، وتفصح عن جميل مكامنه، وقد توصل الباحث إلى مجموعة من النتائج، تتلخص في أن الإمام الكواشي تعرض لأكثر مسائل القراءات في سورة الفاتحة، والمتمثلة في: القراءات الصحيحة والشاذة رواية، وتوجيه القراءات، والتجويد، والوقف والابتداء، ورسم المصحف، وعد الآي، ويوصي الباحث بإجراء دراسات استقرائية تتبع علوم القراءات في هذا الكتاب، ليكون- بذلك- صورة مكتملة لدى المتخصصين في هذا المجال. The research has dealt with modes of recitation issues and their sciences found in the book "Al-Talkhis fi Tafsir Al-Qur'an Al-Aziz"" by Imam Abi Al-Abbas Al-Kawashi (d. 680 AH). Surat Al-Fatihah was taken as a case study where its ayas were studies inductively and descriptively. The most important features of the author's approach in dealing with these issues were illustrated. The problem of the research lies in the many sciences of recitations found in this book, which amount to seven sciences. No previous study has inductively collected, studied and clarified their approaches. Therefore, this research is hoped to pave the way for other studies to reveal the other features and secrets of the book. The researcher concludes with a number of results among which are that Imam Al-Kawashi has made an account of the most issues found in the recitation modes in Surat Al-Fatihah, which are: correct mode of recitation from an abnormal riwayah, interpretation of the qira’ah, tajweed, stopping and starting, script of the Qur’an, ayah counting. Among the recommendations of the study is that more inductive studies should be conducted on the science of qira’at in this book in order to form a complete picture for specialists in this field.
Keywords: علم القراءات -- تفسير القرآن الكريم -- سورة الفاتحة -- الكواشي، أحمد بن يوسف بن الحسن، 680 هـ